2016
DOI: 10.1007/s00417-015-3251-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of vitrectomy for diffuse diabetic macular edema may depend on its preoperative optical coherence tomography pattern

Abstract: Vitrectomy can be a useful treatment option for DDME, particularly for eyes with SRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
1
15
0
3
Order By: Relevance
“…Kaya and Aksoy for their interest and questions regarding our report on the effectiveness of vitrectomy in diffuse diabetic macular edema [1].In our study, we found that vitrectomy was effective for the treatment of diffuse diabetic macular edema, particularly in eyes with subretinal fluid (SRF). As the commenters indicated, SRF may be associated with impairment of the outer blood retinal barrier or of pump function of retinal pigment epithelium (RPE).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Kaya and Aksoy for their interest and questions regarding our report on the effectiveness of vitrectomy in diffuse diabetic macular edema [1].In our study, we found that vitrectomy was effective for the treatment of diffuse diabetic macular edema, particularly in eyes with subretinal fluid (SRF). As the commenters indicated, SRF may be associated with impairment of the outer blood retinal barrier or of pump function of retinal pigment epithelium (RPE).…”
mentioning
confidence: 73%
“…Kaya and Aksoy for their interest and questions regarding our report on the effectiveness of vitrectomy in diffuse diabetic macular edema [1].…”
Section: To the Editormentioning
confidence: 99%
“…In our study, normal fovea contour was found in only 1 case, ERM and SF were found in 2 cases each, and MC, LFD, and SFD were documented after surgery. Although some authors have reported that preoperative OCT findings such as external limiting membrane integrity or presence of subretinal fluids may be closely related to final visual outcome [37,38] , it is important to review and analyze postoperative macular status on OCT after PPV in diabetic macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…101,[209][210][211][212][213][214][215][216] VA improvements however have not been as consistent and as significant as the reduction in retinal thickness following the procedure. 192,203,[217][218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] This discrepancy between anatomical and functional results of vitrectomy for DME may be due to the inherent postoperative ocular sequelae, such as cataract formation that can confound VA interpretations. Also, surgical intervention continues to be reserved for those cases that have had chronic and severe forms of DME when retinal damage is irreversible thereby biasing the results.…”
Section: Surgical Management Of Diabetic Retinopathy and Diabetic Macmentioning
confidence: 99%